2020
DOI: 10.1590/0103-8478cr20200105
|View full text |Cite
|
Sign up to set email alerts
|

Impact of massage on goats on the human-animal relationship and parameters linked to physiological response

Abstract: Considering the benefits that massage can promote, this research aimed to apply the stroking massage in five adult goats (G1-G5) assessed in group and individually for ten days. Parameters related to massage, immune system, physiology and behavior of goats were observed. There was only significant difference (P<0.05) regarding behavior expressed in the presence of the masseur in G4 and G5, between week 1 and 2. Most goats accepted massage, except G2, with greater demonstrations of positive than negative beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the key factor in benefiting from social buffering was not simply the presence of people but rather an active interaction with them. Indeed, research has shown that physical contact with humans has beneficial effects on goats (Leite et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the key factor in benefiting from social buffering was not simply the presence of people but rather an active interaction with them. Indeed, research has shown that physical contact with humans has beneficial effects on goats (Leite et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the provision of the tactile stimuli, a 50 cm flexible rod was used. The tip was covered with cotton fabric, and the cows were rubbed for 07 s across the back and hind limbs of the animal in the neck-tail direction and for 30 s in the udder region; without touching the cows' teats, circular movements were performed using the rod, applying gentle but firm pressure, in accordance with a methodology adapted from [31]. After this, the teat cups were attached to start milking.…”
Section: Tactile Stimulimentioning
confidence: 99%
“…Despite their importance, there are relatively sparse data on these markers, even though they can be used to assess animal stress and welfare objectively [ 5 ]. Experiments on goats [ 20 ] and pigs [ 5 ] carried out to examine the impact of various forms of touch on behavioral and physiological indices, including oxidative stress indicators, did not reveal significant differences. It should be emphasized; however, that the study on goats did not show a negative effect of touch, and the massage protocols applied did not interfere with the homeostasis in these animals [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on goats [ 20 ] and pigs [ 5 ] carried out to examine the impact of various forms of touch on behavioral and physiological indices, including oxidative stress indicators, did not reveal significant differences. It should be emphasized; however, that the study on goats did not show a negative effect of touch, and the massage protocols applied did not interfere with the homeostasis in these animals [ 20 ]. Fear is one of the breed-specific traits and is characterized by a high heritability coefficient [ 21 ].…”
Section: Introductionmentioning
confidence: 99%